PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI - Afifah, Ikrimah Muna Abir; Suwarno, Agus Endro (LPPM Universitas Bina Bangsa, 2024)
This study aims to examine the effect of Good Corporate Governance proxied with independent board of commissioners, audit committee, and institutional ownership on company value proxied with Tobin's Q with profitability proxied with Return On Asset (ROA) as a mediation variable. The population in this study was obtained using purposive sampling method on Banking sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2021 and based on predetermined criteria, a sample of 68 companies was obtained. The analysis method used is path analysis and sobel test with SPSS (Statistical Product and Service Solution) Version 25 application tools. The results of the research analysis prove that: 1) The independent board of commissioners has an effect on profitability, 2) The audit committee has no effect on profitability, 3) institutional ownership has an effect on probability, The independent board of commissioners has an effect on the value of the company, 4) The independent board of commissioners has an effect on the value of the company, 5) The audit committee has no effect on the value of the company, 6) Institutional ownership has an effect on the value of the company, 7) Profitability has no effect on the value of the company, 8) Profitability as a mediating variable is not able to mediate the influence of the variable of the independent board of commissioners on the value of the company, 9) Profitability as a mediating variable is not able to mediate the effect of audit committee variables on company value, 10) Profitability as a mediation variable is not able to mediate the influence of institutional ownership variables on company value